Encouragement of Cross-Curricular Competencies in Geography Education - Schrüfer, Gabriele (Journal of Geography Education, 2009)
Over the past years the term intercultural learning was almost inflationary used by many fields. Both discussions in education which naturally influences geography education illustrate that the term is not well-defined. Besides, not only the intentions are determined partly different but also many curriculum and textbooks differ about the transfer. In newer literature cross-cultural competence is considered as the aim of intercultural learning, but nonetheless it is barely described how and with which steps this aim can be accomplished consistently. The developmental model of intercultural sensitivity, a model by Bennett (1993) for developing cross-cultural competence, could be helpful for realizing this in geographic teaching. This paper introduces this model after an overview of the discussion in education and teaching geography and discusses possible consequences for geography education.